Dynamic performance of tire-granular material composite foundation subjected to axial and low frequency horizontal cyclic reversed loadings. Issue 8 (11th June 2022) - Wang, Fengchi; Nie, Xiaomei; Hu, Haiming; Zhao, Hanyu
Abstract: Buildings in towns and villages suffer heavy damages and losses during earthquakes. In this study, six types tire–granular material composite foundations were fabricated and tested under cyclic reversed loading to investigate the energy absorption and dissipation effects of such composite foundations applied to village buildings. The effects of different axial loads (100, 200 and 300 kPa), tire arrangement and transverse connection between layers on the dynamic performance of the tire–granular material composite foundations were examined. The failure patterns of the composite foundation were obtained. The effects of the aforementioned design parameters on the dynamic performance of the composite foundation, characterised by the hysteresis loops, skeleton curves, stiffness degradation curves and energy dissipation capacity, were analysed. The hysteresis loops were full, indicating good seismic performance. The results demonstrated that using a staggered lap joint arrangement and adding a fibre mesh improved the horizontal bearing capacity and lateral stiffness of the composite foundation and enhance its overall damping capacity. Therefore, adding space connections between tires can improve the energy dissipation capacity of the foundation.